The Influence Of Discounts And Brand Awareness Mediated By Buying Intention On Buying Decisions For Domino's Pizza Products - Nababan, Henry Fransisko Paniroi; Erika Hardiyanti Kusuma Dewi; Retno Purwani Setyaningrum (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study examines the influence of discount promotions and brand awareness on consumer purchasing decisions for Domino's Pizza in Bekasi Regency, with purchase intention as a mediating variable. Using a quantitative approach, 384 respondents were surveyed through accidental sampling. Data analysis using Smart PLS 3.0 revealed that both discount promotions and brand awareness significantly impact purchasing decisions, with purchase intention mediating these relationships. All indicators proved valid and reliable, with hypothesis testing showing statistical significance. The findings highlight the importance of promotional elements in marketing strategies and support previous research on the subject. Companies are advised to focus on these elements to enhance customer satisfaction and loyalty. This research provides valuable insights for marketers in the fast-food industry, particularly in the Indonesian market, and lays groundwork for future studies in consumer behavior.